THE EFFECT OF REWARD SYSTEMS, WORK ENVIRONMENT, AND DISCIPLINE ON EMPLOYEE PERFORMANCE IN EDUCATIONAL INSTITUTIONS: AN EMPIRICAL AND MANAGERIAL PERSPECTIVE - Sindi Prati Minanda; Tanto G. Sumarsono; Nanik Sisharini; Krisna Veda Aryaputra (INTERNATIONAL JOURNAL OF SOCIETY REVIEWS, 2025)
This study aims to examine the influence of reward and work environment on employee performance through work discipline at BMB Air-Langga, an educational institution. A total of 84 permanent employees participated in the research, providing data through structured questionnaires using a five-point Likert scale. The validity and reliability of the instruments were verified using SPSS version 25, employing Pearson correlation for validity and Cronbach’s Alpha for reliability (α > 0.70). Descriptive analysis was conducted to assess respondents’ perceptions of the variables, while inferential analysis via path analysis with SPSS was used to investigate the causal relationships among reward, work environment, work discipline, and employee performance. The results reveal that both reward and work environment positively and significantly impact employee performance, both directly and indirectly through work discipline as a mediating variable. The findings support the theoretical premise that effective human resource management practices, including fair compensation and a supportive work environment, enhance employee discipline and motivation, ultimately leading to improved performance. This research contributes practical insights for organizational leaders seeking to optimize performance through targeted HR strategies, utilizing SPSS in quantitative analysis to ensure robust and valid conclusions.